1997
DOI: 10.1021/jp970046n
|View full text |Cite
|
Sign up to set email alerts
|

Semiempirical Correlation between Optical Band Gap Values of Oxides and the Difference of Electronegativity of the Elements. Its Importance for a Quantitative Use of Photocurrent Spectroscopy in Corrosion Studies

Abstract: A semiempirical correlation between the optical band gap of binary oxides and the difference of electronegativity between the oxygen and metallic elements (Pauling's extraionic energy) is proposed. In the frame of the proposed correlation an estimate of the repulsive term in the total lattice energy of ionic oxides is obtained in very good agreement with the existing data. An extension of the correlation to the ternary oxides and hydroxides is proposed by using the concept of average cationic or anionic group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
156
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(167 citation statements)
references
References 38 publications
11
156
0
Order By: Relevance
“…In any case, in presence of a steady-state (anodic/cathodic) photocurrent, a tunnelling process across the inner MgO film of photogenerated carriers (electrons/holes) must be assumed at the inner interface, according to the bilayer structure of Fig. 21b, where a band gap of 7.8 eV has been assumed for MgO, in agreement with the value reported in literature [21].…”
Section: Anodic Filmssupporting
confidence: 76%
See 1 more Smart Citation
“…In any case, in presence of a steady-state (anodic/cathodic) photocurrent, a tunnelling process across the inner MgO film of photogenerated carriers (electrons/holes) must be assumed at the inner interface, according to the bilayer structure of Fig. 21b, where a band gap of 7.8 eV has been assumed for MgO, in agreement with the value reported in literature [21].…”
Section: Anodic Filmssupporting
confidence: 76%
“…The possibility of band to band optical transitions has been neglected, considering that cathodic photocurrent at photon energy much less than the band gap of MgO (E g = 7.8-8.7 eV, see Refs. [21,22]) or Mg(OH) 2 (E g = 4.25 eV, see below) was measured at U OC or more cathodic potentials. Fig.…”
Section: Pcs Characterization Of Mechanical Treated Electrodes In Aqumentioning
confidence: 99%
“…This was ascribed to the lower Ta-O-Ta bond angle of LiTaO 3 (143 • ), with respect to NaTaO 3 (163 • ) and KTaO 3 (180 • ). This inhibits the charge migration [212].…”
Section: Photoreforming Of Carbohydratesmentioning
confidence: 99%
“…NiO was also tested under the same conditions for the PR of methanol and higher alcohols [142]. It is p-type semiconductor with a bandgap energy of 3.5 eV and the potentials of the valence and conduction band edges at +3.0 and −0.5 V, respectively [143]. Absorption of a photon of suitable energy (E > E g ) causes the transfer of an electron from the valence band of oxygen (2p) to the conduction band of Ni (3d) atom and in turn the reduction of Ni 2+ to Ni + .…”
Section: Photoreforming Of Alcoholsmentioning
confidence: 99%
“…It is within the aims of this chapter to show that it is possible to relate the band gap values of numerous oxides to their composition by means of a semiempirical approach. In a previous work 137 it has been shown that such a task could be accomplished by proposing the following general correlation between the band gap of crystalline oxides and the difference of electronegativity of their constituents:…”
Section: Band Gap and Oxide Film Composition (I) Binary Crystalline Omentioning
confidence: 99%